Prospective analysis of the effects of maternal immune activation on rat cytokines during pregnancy and behavior of the male offspring relevant to Schizophrenia - Lins, Brittney; Hurtubise, J.L.; Roebuck, A.J.; Marks, W.N.; Zabder, N.K.; Scott, G.A.; Greba, Q.; Dawicki, W.; Zhang, X.; Rudulier, C.D.; Gordon, J.R.; Howland, J.G. (2018)
© 2018 Lins et al. Influenza during pregnancy is associated with the development of psychopathology in the offspring. We sought to determine whether maternal cytokines produced following administration of viral mimetic polyinosinic-polycytidylic acid (polyI:C) to pregnant rats were predictive of behavioral abnormalities in the adult offspring. Timed-pregnant Sprague Dawley rats received a single intravenous injection of 4-mg/kg polyI:C or saline on gestational day (GD)15. Blood was collected 3 h later for serum analysis of cytokine levels with ELISA. Male offspring were tested in a battery of behavioral tests during adulthood and behavior was correlated with maternal cytokine levels. Maternal serum levels of CXCL1 and interleukin (IL)-6, but not tumor necrosis factor (TNF)-α or CXCL2, were elevated in polyI:C-treated dams. PolyI:C-treated dams experienced post-treatment weight loss and polyI:C pups were smaller than controls at postnatal day (PND)1. Various behavior alterations were seen in the polyI:C-treated offspring. Male polyI:C offspring had enhanced MK-801-induced locomotion, and reduced sociability. PolyI:C offspring failed to display crossmodal and visual memory, and oddity preference was also impaired. Set-shifting, assessed with a lever-based operant conditioning task, was facilitated while touchscreen-based reversal learning was impaired. Correlations were found between maternal serum concentrations of CXCL1, acute maternal temperature and body weight changes, neonatal pup mass, and odd object discrimination and social behavior. Overall, while the offspring of polyI:C-treated rats displayed behavior abnormalities, maternal serum cytokines were not related to the long-term behavior changes in the offspring. Maternal sickness effects and neonatal pup size may be better indicators of later effects of maternal inflammation in the offspring.